Histopathology-based immunoscore predicts recurrence for intrahepatic cholangiocarcinoma after hepatectomy - Tian, Meng-Xin; Zhou, Yu-Fu; Qu, Wei-Feng; Liu, Wei-Ren; Jin, Lei; Jiang, Xi-Fei; Wang, Han; Tao, Chen-Yang; Zhou, Pei-Yun; Fang, Yuan; Ding, Zhen-Bin; Peng, Yuan-Fei; et al. (Cancer Immunology, Immunotherapy, 2019)
Intrahepatic cholangiocarcinoma (ICC) is a rare malignancy with poor prognosis. The evaluation of recurrence risk after liver resection is of great importance for ICCs. We aimed to assess the prognostic value of intra- and peritumoral immune infiltrations and to establish a novel histopathology-related immunoscore (HRI) associated with ICC recurrence. A total of 280 ICC patients who received curative resection between February 2005 and July 2011 were enrolled in our study. Patients were randomly assigned to the derivation cohort ( n = 176) or the validation cohort ( n = 104). Sixteen immune biomarkers in both intra- and peritumoral tissues were examined by immunohistochemistry. The least absolute shrinkage and selection operator (LASSO) Cox model was used to establish the HRI score. Cox regression analysis was used for multivariate analysis. Nine recurrence-related immune features were identified and integrated into the HRI score. The HRI score was used to categorize patients into low-risk and high-risk groups using the X-tile software. Kaplan–Meier analysis presented that the HRI score showed good stratification between low-risk and high-risk groups in both the derivation cohort ( P < 0.001) and the validation cohort ( P = 0.014), respectively. Multivariate analysis demonstrated that serum γ-glutamyl transpeptidase, carbohydrate antigen 19-9, lymphoid metastasis, tumor numbers, and the HRI score were independent risk factors associated with recurrence-free survival (RFS). The combination of Shen’s model and HRI score provided better performance in recurrence prediction compared with traditional staging systems. The HRI score might serve as a promising RFS predictor for ICC with prognostic values.